Code like a pro in C# - Rodenburg, Jort (Manning Publications, 2021)
Worth reading multiple times. Prabhuti Prakash, Synechron Technologies In Build on your existing programming skills and upskill to professional-level C# programming. Code Like A Pro in C# you will learn: Unit testing and test-driven development Refactor a legacy .NET codebase Principles of clean code Essential backend architecture skills Query and manipulate databases with LINQ and Entity Framework Core Critical business applications worldwide are written in the versatile C# language and the powerful .NET platform, running on desktops, cloud systems, and Windows or Linux servers. Code Like a Pro in C# makes it easy to turn your existing abilities in C# or another OO language (such as Java) into practical C# mastery. There's no "Hello World" or Computer Science 101 basics--you'll learn by refactoring an out-of-date legacy codebase, using new techniques, tools, and best practices to bring it up to modern C# standards. about the technology You know the basics, now get ready for the next step! Pro-quality C# code is efficient, clean, and fast. Whether you're building user-facing business applications or writing data-intensive backend services, the experience-based, practical techniques in this book will take your C# skills to a new level. about the book Code Like a Pro in C# teaches you to how write clean C# code that's suitable for enterprise applications. In this book, you'll refactor a legacy codebase by applying modern C# techniques. You'll explore tools like Entity Framework Core, design techniques like dependency injection, and key practices like testing and clean coding. It's a perfect path to upgrade your existing C# skills or shift from another OO language into C# and the .NET ecosystem. about the audience For developers experienced with object-oriented programming. No C# experience required. about the author Jort Rodenburg is a software engineer who has taught numerous courses on getting up to speed with C# and .NET. Packed with guidance and insights to get you there quickly. Highly recommended! Edin Kapic, isolutions This book really helped me to move to the next level. Daniel Vásquez Estupiñan, Tokiota This is the book you are looking for when you want to know how to code in the most idiomatic way possible with C#.
Online resource; title from title details screen (O'Reilly, viewed May 2, 2022)
Keywords: Microsoft .NET Framework; C# (Computer program language); Object-oriented programming languages; Relational databases; Internet programming; Application software -- Development; C# (Langage de programmation); Langages orientés objet (Informatique); Bases de données relationnelles; Programmation Internet; Logiciels d'application; Développement; Application software; Development; Downloadable audio books; Audiobooks; Livres audio